Humidity Sensing Properties of Zinc Oxide-indigo Dye Nanocomposite - Tariq Saeed Chani, Muhammad; Bahadar Khan, Sher; M. Asiri, Abdullah; Saeed, Ghuzanfar; Nadeem Arshad, Muhammad (Current Nanoscience, 2016)
The zinc oxide-indigo dye nano-composite based smart humidity sensors have been fabricated and investigated. A novel instrument-less technique has been used to fabricate these sensors, where the aluminium electrodes are fixed on the glass substrate without involving any chemical or physical process. The size of each electrode is 5x10 mm2 and the gap between two electrodes is 40 μm. To deposit the active films the ZnO-indigo dye nanocomposite has been prepared by using solution method and films of 20 to 60 μm thicknesses are deposited by drop casting. The fabricated sensors have been tested in the range of 10% to 90% relative humidity (RH). It is observed that the capacitive and resistive sensitivities are 5x103pF/%RH and -154.3MΩ/%RH, respectively. This behavior may be attributed to absorption and adsorption of water molecules which absorb to the active film’s surface. The effects of frequency (measuring) and film thickness on the sensor’s performance have been studied and the results show that with rise in frequency and increase in thickness the sensor’s initial resistance decreases. The experimental results are simulated by using an exponential function and simulated results are well matched with experimental results.
Keywords: zinc oxide